2004
DOI: 10.1111/j.0030-1299.2004.13250.x
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking plant community theory

Abstract: International audiencePlant communities have traditionally been viewed as either a random collection of individuals or as organismal entities. For most ecologists however, neither perspective provides a modern comprehensive view of plant communities, but we have yet to formalize the view that we currently hold. Here, we assert that an explicit re-consideration of formal community theory must incorporate interactions that have recently been prominent in plant ecology, namely facilitation and indirect effects am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
446
0
20

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 506 publications
(479 citation statements)
references
References 41 publications
13
446
0
20
Order By: Relevance
“…In natural conditions, properties of plant communities such as composition and structure arise from the interaction of both coarse-and fine-scale filters (Dale, 1999;Lortie et al, 2004). On a fine scale, vegetation patterns are ruled by species size and growth pattern, as well as by the interactions among plant individuals.…”
Section: Emergent Properties: the "Pattern Of Spatial Occupancy"mentioning
confidence: 99%
“…In natural conditions, properties of plant communities such as composition and structure arise from the interaction of both coarse-and fine-scale filters (Dale, 1999;Lortie et al, 2004). On a fine scale, vegetation patterns are ruled by species size and growth pattern, as well as by the interactions among plant individuals.…”
Section: Emergent Properties: the "Pattern Of Spatial Occupancy"mentioning
confidence: 99%
“…Earlier theories propose a continuum along which the assembling of species is determined by stochastic events (e.g. dispersal limitation) at large spatial scale (landscape, km 2 >), while at more local scale (m 2 -km 2 ) deterministic processes are ruling species assemblage (Lortie et al 2004;Gravel et al 2006). In dry semi-natural grassland in south-western Sweden, this pattern was effectively observed among a series of leaf and whole-plant traits comparing landscape scales with patch scales (de Bello et al 2013).…”
Section: Which Assembly Process For Which Conditions?mentioning
confidence: 99%
“…Neutral theory (6)(7)(8) suggested that species-specific differences are unimportant for certain community attributes, whereas niche theory outlines the importance of species characteristics and trade-offs (9,10). It is also clear that species-specific differences affect the spatial distribution of populations (11)(12)(13)(14)(15)(16). Surprisingly, although plant-plant interactions should play a major role in structuring tropical forests, the resulting spatial patterns in diversity have not been analyzed from the viewpoint of individual species.…”
mentioning
confidence: 99%